PENGARUH MEDIA PEMBELAJARAN AUGMENTED REALITY BERBANTUAN APLIKASI ASSEMBLR EDU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI KELAS IV SDN 101812 NAMO TUALANG - Christina, Theresia; Betarapita Silalahi; Umar Darwis; Tiflatul Husnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Augmented Reality (AR) learning media assisted by the Assemblr Edu application on students' learning outcomes in the IPAS subject on the topic Plants as a Source of Life on Earth. The research employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 45 fourth-grade students at SDN 101812 Namo Tualang, divided into 22 students in the experimental class (using AR media) and 23 students in the control class (conventional learning). The research instrument was an essay test consisting of 12 valid questions (reliability α = 0.952). Data analysis was conducted using the Mann-Whitney U test and independent sample t-test. The results showed a highly significant difference between the two groups, with the post-test scores of the experimental class (M = 88.27) being higher than those of the control class (M = 76.04). The Mann-Whitney U test produced Z = -5.736 with p < 0.001, while the t-test resulted in t = 10.363 with p < 0.001 and Cohen’s d effect size = 3.090 (very large). These findings indicate that Augmented Reality learning media supported by the Assemblr Edu application significantly improves students' learning outcomes on the topic Plants as a Source of Life on Earth. AR media effectively visualizes abstract concepts in a more concrete and interactive manner, thereby enhancing students’ understanding and learning achievement in IPAS.